2022
DOI: 10.21203/rs.3.rs-2319768/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Unplanned Pregnancy on the Initiation of Intimate Partner Violence in Southeast Iran

Abstract: Background:Violence during pregnancy may lead to pregnancy complications or adverse birth outcomes or other serious reproductive events. Unplanned pregnancy can lead to a wide range of physical and psychological consequences for mother and child and affects different aspects­ of social, economic and cultural health. The aim of study is to find if unplanned pregnancy can cause intimate partner violence. Methods: This cross-sectional descriptive research was carried out with available sampling on 300 eligible wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Shammin et al (2008) analyzed 244 cases of gingival lesions at the Department of Oral Pathology, Government Dental College, Calicut, India, and reported that non-neoplastic lesions comprised 75.5% of the cases, out of which PG accounted for 52.7%. A descriptive study of 923 Iranian pregnant women revealed that only 2 of them (0.22%) presented with PG [15]. On the other hand, a 4.2% PG prevalence has been reported in this group of patients in a medical center in Kerman/Iran [16].…”
Section: Epidemiologymentioning
confidence: 99%

Oral Pyogenic Granuloma: A Literature Review

Lomeli Martinez,
Carrillo Contreras,
Gómez Sandoval
et al. 2023
Preprint
“…Shammin et al (2008) analyzed 244 cases of gingival lesions at the Department of Oral Pathology, Government Dental College, Calicut, India, and reported that non-neoplastic lesions comprised 75.5% of the cases, out of which PG accounted for 52.7%. A descriptive study of 923 Iranian pregnant women revealed that only 2 of them (0.22%) presented with PG [15]. On the other hand, a 4.2% PG prevalence has been reported in this group of patients in a medical center in Kerman/Iran [16].…”
Section: Epidemiologymentioning
confidence: 99%

Oral Pyogenic Granuloma: A Literature Review

Lomeli Martinez,
Carrillo Contreras,
Gómez Sandoval
et al. 2023
Preprint